ANALISIS KEMAMPUAN SISWA KELAS V SDN DALAM MERENCANAKAN DAN MENGEVALUASI PENYELIDIKAN ILMIAH MATERI GAYA MAGNET - Boleng, Jaclyne Stefini Doni; Rusamawan (STKIP Subang, 2026)
Scientific literacy is an essential competence in elementary science education, particularly in relation to students’ ability to plan and evaluate scientific investigations. However, previous studies indicate that these inquiry skills have not been optimally developed among elementary students. This study aimed to describe fifth-grade students’ ability to plan and evaluate scientific investigations in science learning on magnetic force material. A quantitative descriptive method was employed without experimental treatment. The study was conducted at SD Negeri Sokowaten, Bantul Regency, Yogyakarta Special Region, involving 50 fifth-grade students selected using cluster sampling. Data were collected through a test instrument designed to measure students’ abilities in planning and evaluating scientific investigations and were analyzed using descriptive statistics and non-parametric analysis. The results revealed that students’ ability to plan scientific investigations was generally in the low to moderate category, particularly in formulating investigable questions and designing experiments. In contrast, students demonstrated relatively better ability in evaluating scientific investigations, although difficulties were still found in interpreting data. Overall, the findings indicate that students’ scientific inquiry abilities have not yet developed evenly. Therefore, strengthening inquiry-based science learning is necessary to support the balanced development of students’ scientific literacy.